Chasing the demon [large type] : a secret history of the quest for the sound barrier, and the band of American aces who conquered it - Hampton, Dan (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"In 1947, the United States Air Force was established. Meanwhile, scientists and engineers were pioneering a revolutionary new type of aircraft which could do what no other machine had ever done: reach mach 1--a speed faster than the movement of sound--which pilots called "the demon." Chasing the Demon recreates an era of excitement and danger, adventure and innovation, when the future of the free world was at stake and American ingenuity took the world from the postwar years to the space age. While the pressure to succeed was high, it was unknown whether man or machine could survive such tremendous speeds. A decorated military pilot with years of experience flying supersonic fighter jets, Dan Hampton reveals in-depth the numerous potential hazards that emerged with the Air Force's test flights: controls broke down, engines flamed out, wings snapped, and planes and pilots disintegrated as they crashed into the desert floor. He also introduces the men who pushed the envelope taking the cockpits of these jets, including World War II ace Major Dick Bong and twenty-four-year-old Captain Chuck Yeager, who made history flying the Bell X-1 plane faster than the speed of sound on October 14, 1947."--